KINERJA BUPATI BATANG TAHUN 2012 - Febrianto, Anggara; Adhi, Suwanto; Utomo, Susilo (Journal of Politic and Government Studies, 2014)
In 2011, Yoyok Riyo Sudibyo was being elected as Batang‘s Regent. He tagged ―Clean Bureaucracy and Growing Economy‖ vision in running his government for 5 years ahead. He started the 2012 by focusin on enhancing the quality of public service, infrastructure and the government accountability.Contrary, we find out there is lack of good governance in Batang‘s Regency during 2012. Some reasons are residents are being not pleased with the Government plan in developing the regency; also the government never reaches an agreement with the legislative for its own budget and masterplan. Vividly, those complicated events are becoming an obstacle for the government. Moreover the legitimation of the regent is also being questioned by his lack of ability in maintaining its own government.The purpose of the research is to understand the performance of Batang‘s Regent while running its Government during 2012.The performance evaluation indicators are taken from the Dwiyanto‘s theorem, those are: productivity, accountability, transparancy, reponsivity, and responsibility. The research is conducting by using the descriptive basis while the supporting data are analyzed qualitatively. The object‘s of the research is the Batang‘s Regent performance for the year 2012.The research concludes that the Regent‘s performance during a year is qualitatively reasonable for being marked as good. The purpose is, the optimum effort that already being given by the regent to reach its own goal—the government‘s vision. Some government supporting departments also reach a significant performance improvement during his leadership. However, we still find some governance failure during a period.Keywords : Regent Performance, Performance Assessment, Realization